Clinical-genetic and Psychoemotional Peculiarities and the Quality of Life of Patients with Long-term Observation of the Dynamics of the Duodenal Ulcer - V. Volevach, Larisa; V. Gabbasova, Liliya; Sh. Nafikova, Aigul; R. Basharova, Guzel; A. Kamalova , Alisa; D. Guryev, Rostislav (International Journal of Psychosocial Rehabilitation, 2020)
The rationale for the present study is explained by a high rate of complications in patients with duodenal ulcers and the necessity to search for the markers of disease development and to study the risk factors. The study is aimed at the evaluation of clinical-genetic and psychoemotional peculiarities and quality of life of patients with duodenal ulcers. The authors examined 231 patients aged 39.8±0.8 years old. The authors evaluated the peculiarities of a social factor with the screening methods, peculiarities of the clinical picture according to the standards, analyzed the polymorphic variants of IL10 (-627С>A; rs1800872) with polymerase chain reaction, and assessed the psychoemotional status and quality of life during a long-term observation after the person-oriented educational program for patients with ulcer disease. The authors revealed the peculiarities of the social factor, the changes in the clinical, endoscopic, and psychoemotional picture of the disease, identified the markers of the development of duodenal ulcerous disease, and registered the improvement of the quality of life. The performance of genetic tests for patients, along with clinical and psychoemotional examinations and positive changes in the quality of life, contribute to the complex approach to a long-term observation of patients with duodenal ulcers.